Punching behaviour of column-slab connection strengthened with non-prestressed or prestressed FRP plates. (1st April 2018) - Abdullah, A.; Bailey, C.G.
Highlights: Prestressed FRP plates reduce deflection and onset of cracking. High strain levels in EBR, due to prestressing, speeds debonding failure. Modelling mixed mode behaviour is essential in capturing debonding failure. Design of FRP RC can be controlled by the serviceability limit state. Abstract: Fracture resistance of concrete column-slab connections, with low reinforcement ratios and strengthened by carbon fibre reinforced polymer (CFRP) plates, is often governed by debonding failure modes. In this paper, a three-dimensional finite element model is conducted to predict the punching behaviour of concrete column-slab connections which incorporate bonded non-prestressed and prestressed CFRP plates to the tension surface of the slab. The adopted interfacial behaviour, between the FRP materials and concrete, takes into account the effect of mixed mode behaviour on the displacement fields at the critical diagonal cracks (CDC). Results are then presented in terms of the ultimate load capacities, load-strain relationships in the FRP and internal steel reinforcement, load-interfacial stress relationships, and stress distributions in the FRP reinforcement. It can be stated that by adopting the mixed mode behaviour at the interface between the fibres and concrete, the onset of debonding is effectively captured by the FE analysis, which is very difficult in a laboratory test.